2007
DOI: 10.1021/ar7001107
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydrogenation Using Monodentate Phosphoramidite Ligands

Abstract: Monodentate phosphoramidites are excellent ligands for Rh-catalyzed asymmetric hydrogenations of substituted olefins. Enantioselectivities between 95 and 99% were obtained in the asymmetric hydrogenation of protected alpha- and beta-dehydroamino acids and esters, itaconic acid and esters, aromatic enamides, aromatic enol esters, aromatic and aliphatic enol carbamates, and alpha-substituted cinnamic acids. An iridium catalyst Ir(L*)(COD)Cl was developed that contains only a single bulky phosphoramidite based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
112
0
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 374 publications
(120 citation statements)
references
References 49 publications
0
112
0
5
Order By: Relevance
“…[12] Monodentate phosphoramidite ligands have the advantage of being readily accessible, highly diverse, air stable and inexpensive compared to most bidentate ligands. [13] In addition, they are amenable to parallel synthesis. [14] We have developed the use of monodentate phosphoramidites as ligands for asymmetric hydrogena-tion, [15][16][17] conjugate addition [18] , allylic alkylation, [19] asymmetric arylation of aldehydes, [20] ketones [21,22] and substituted imines.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Monodentate phosphoramidite ligands have the advantage of being readily accessible, highly diverse, air stable and inexpensive compared to most bidentate ligands. [13] In addition, they are amenable to parallel synthesis. [14] We have developed the use of monodentate phosphoramidites as ligands for asymmetric hydrogena-tion, [15][16][17] conjugate addition [18] , allylic alkylation, [19] asymmetric arylation of aldehydes, [20] ketones [21,22] and substituted imines.…”
Section: Introductionmentioning
confidence: 99%
“…42 Two isotopic labeling experiments were carried out to confirm that the simple unprotected indole can be activated by a BrĂžnsted acid to form iminium in situ, which was then hydrogenated by the Pd-catalyst. The use of deuterated TFE afforded the product with two deuterium atoms incorporated to the 3-position which indicated that a reversible process of protonation and deprotonation existed (eqn (9)). Owing to the fact that equilibrium was faster than hydrogenation, thus two deuterium atoms were imported to the 3-position of the 2-methylindoline before hydrogenation occurred.…”
Section: Scheme 21mentioning
confidence: 99%
“…To counter this problem, we have developed a new class of low cost ligands for asymmetric hydrogenation that can be prepared in just two steps. Binol-based monodentate phosphoramidites can be synthesised in a mere 2 steps, making them not only highly cost-effective but also readily prepared in a short period of time even in kg amounts [4]. In addition, their easy preparation allows the parallel synthesis of 96 ligands simultaneously in high throughput equipment, enabling the synthesis and testing of these ligands within 2 days [5].…”
Section: Introductionmentioning
confidence: 99%